THE PROVENANCE AND DIAGENESIS OF SANDSTONES OF THE EOCENE TANJUNG FORMATION IN THE KUALAKURUN AREA, CENTRAL KALIMANTAN - Heryanto, Rachmat; Margono, Untung (Pusat Survei Geologi, 2008)
Kualakurun area is located in the western margin of Tertiary Barito Basin. The basin was filled by the Eocene Tanjung Formation consisting of conglomerate and sandstone in the lowerpart, mudstone within tercalated by coal seams in the middle part, and sandstones in the upper part. The sandstones consist of subarkose, sub litharenite, and felspathi clitharenite. The framework grains dominantly consist of quartz with some lithic and feldspar fragments.The accessory minerals are muscovite and opaque minerals. The provenance of sandstone fragments of theTanjung Formation were derived from Continental Block (Craton Interior) and Recycled Orogen (Quartzose Recycled), which mostprobably were derived from the pre-Tertiary rocks of the Schwaner Mountains (Cretaceous granites and tonalities intruding Silurian-Permian metamorphic rocks) in the west of the Kualakurun area. Diagenetic processes identified in the sandstones are compaction, mineral authigenic and secondary porosity formations. The diagenesis regimeis categorizedas “mesogenesis mature A”, that is equal to mudrocks tageII, having apaleo-temperature of 80°upto95°C,and the burial depth ranging from2to3 kilometers. Keyword: provenance, sandstone, diagenesis, Tanjung Formation, Kualakurun